Cleft palate associated with Turner's syndrome and anterior cervical hypertrichosis - Anil Kumar Desai; Niranjan Kumar; Sameer Pandey; Sandhya S Pavate (Wolters Kluwer Medknow Publications, 2017)
Turner's syndrome is a rare genetic disorder that affects development in female. It is associated with multiple medical issues such as impaired growth, ovarian insufficiency, cardiovascular abnormalities, and endocrine and skeletal abnormalities. Hypertrichosis is the growth of an increased quantity of thick hair on any part of the skin surface; it is mostly seen as an isolated finding but rarely associated with other abnormalities. Cleft lip and palate are uncommon anomalies in Turner's syndrome and anterior cervical hypertrichosis. We report a case of cleft palate associated with Turner syndrome and anterior cervical hypertrichosis. The clinical features, diagnosis, and its management are discussed.